Labor market institutions and the incidence of payroll taxation - KIM, Jinyoung (Institutional Knowledge at Singapore Management University, 2022)
Despite the unambiguous predictions of the canonical model of a competitive labor market, empirical studies of the labor market effects of payroll taxation provide conflicting evidence. We estimate the labor market impacts of payroll taxation in Singapore, the country with the most competitive and flexible labor market among the countries investigated in the literature. By exploiting the sharp reduction in payroll tax rate when workers turn 60, we find that the reduced payroll tax rate in Singapore has a large effect on wages without changes in employment. Our meta-analysis shows consistent evidence that varying degrees of labor market competitiveness across places and time could explain the mixed results in the literature. Our findings corroborate the prediction of the canonical model that the welfare costs of social insurance programs financed by payroll taxes can be small in a competitive labor market.